Alumina-based composite sol composition, method for producing the same, and method for producing an alumina-based composite film
By using alumina composite solution compositions, the solution-gel method is used to create aluminum oxide composite film at lower temperatures, which solves the problem of dense structures and cracks at low temperatures at low temperatures, and achieves insulation and insulation and realization of insulation and realization. Pine film manufacturing with high hardness is suitable for various substrates.
Patent Information
- Application Number
- CN202180079132.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-09
- Filing Date
- 2021-11-09
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-11-09
AI Technical Summary
When the existing alumina sols form films with high insulation and hardness, it is difficult to achieve a dense structure at a lower temperature, and there are crack problems, which limits its application range.
The aluminum oxide composite composite composition containing aluminum oxide hydraulic, alkoxyxyxo, diverse organic acid and solvents is used to create an aluminum oxide composite film with an insulating and high hardness at a lower temperature at a lower temperature. Essence
It is possible to produce an alumina-based composite film with high insulation and hardness at a relatively low temperature. It has excellent adhesion to the substrate and is suitable for various substrates.
Smart Images

Figure BDA0004245899030000161 
Figure BDA0004245899030000162 
Figure BDA0004245899030000181
Abstract
Description
Technical Field
[0001] The present invention relates to an alumina composite sol composition for forming an alumina composite thin film, a method for producing the same, and a method for producing the alumina composite thin film. The present invention also relates to an alumina sol and a method for producing the same. Background Art
[0002] Alumina sol can be produced by wet methods such as sol-gel method, and its production methods are complex and diverse. Alumina sol is used for various purposes, such as thickener, suspending agent, catalyst, polymer reinforcing agent, binder, surface modifier of metal, inorganic powder, porous carrier, etc., porous self-supporting film, film formed on substrate, and adsorbent for water treatment. The alumina hydrate particles contained in the alumina sol have various shapes such as plate, column, needle, particle, fiber, etc. The physical properties of the alumina sol vary depending on the shape of the alumina hydrate particles, and the use also varies according to its physical properties.
[0003] It is known that an insulating film is formed on the substrate surface in order to impart insulation to substrates such as metals and graphite. In addition, it is known that a transparent film with a hard coating function is formed on the substrate surface in order to improve the scratch resistance of substrate surfaces such as glass, plastic sheets, plastic lenses, display devices, etc.
[0004] As a method for producing a thin film of a metal oxide, there are gas phase processes such as PVD method and CVD method and liquid phase processes such as sol-gel method and electrophoresis method.
[0005] Patent document 1 discloses a coating composition as a coating composition capable of forming an aluminum oxide film having excellent film-forming properties, density, gas barrier properties, thermal stability, electrical insulation, antifouling properties, antistatic properties, etc. by a sol-gel method, characterized in that it contains an aluminum oxide sol and an alkoxysilane compound, wherein the aluminum oxide sol is obtained by hydrolysis of aluminum alkoxide and contains fibrous or needle-shaped aluminum oxide hydrate particles or aluminum oxide particles with a short diameter of 1 to 10 nm, a long diameter of 100 to 10,000 nm and an aspect ratio (long diameter / short diameter) of 30 to 5,000, and the alkoxysilane compound is present in an amount of 5 to 2,000 parts by mass relative to 100 parts by mass of the aluminum oxide hydrate particles or aluminum oxide particles.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2013-216760 Summary of the invention
[0009] Problems to be solved by the invention
[0010] In order to obtain a film with high insulation properties as an insulating coating and a film with high hardness as a hard coating, a dense structure with sufficiently small pores and no cracks in the coating film is required. Alumina sols previously used are mostly in the shape of diamond, chestnut, deformed spherical, columnar, etc., and the adhesion between particles is poor. In such sols, the particles are not densely connected, making it difficult to cover the entire surface of the substrate.
[0011] On the other hand, the sol-gel method, which is one of the methods for manufacturing a thin film of metal oxide, can carry out all its processes under normal pressure, and the number of processes is also small, so it is a cheap and simple method compared with the gas phase method (PVD, CVD, etc.) and the electrophoresis method. However, there is a problem that cracks are easily generated in the film due to the shrinkage of the metal oxide during the volatilization of the solvent of the coating composition. In addition, in the sol-gel method, in order to manufacture a dense film without pores, it is necessary to heat treat the coating composition at a temperature above 500°C after applying it to the substrate, so there are restrictions on the material of the substrate to be used.
[0012] When the coating composition described in Patent Document 1 is used to produce an aluminum oxide film, it is heat treated at a wide range of temperatures, for example, 50°C to 1500°C, depending on the substrate and purpose of application. However, in order to impart insulation properties, heat treatment at a temperature of at least 300°C is required.
[0013] Therefore, an object of the present invention is to provide a coating composition that can produce an aluminum oxide-based thin film having high insulation properties and hardness by heat treatment at a relatively low temperature using a sol-gel method.
[0014] Means for solving problems
[0015] The specific means for solving the above-mentioned problems are as follows.
[0016] A first embodiment of the present invention is the following alumina-based composite sol composition.
[0017] (1) An alumina-based composite sol composition comprising (A) an alumina sol containing alumina hydrate, (B) an alkoxysilane compound, (C) a polybasic organic acid, and (D) a solvent, wherein the amount of alumina hydrate in the (A) alumina sol is 3% by mass to 11% by mass.
[0018] (2) An alumina-based composite sol composition comprising (A) an alumina sol containing alumina hydrate, (B) an alkoxysilane compound, (C) a polybasic organic acid, and (D) a solvent, wherein the amount of alumina hydrate in the alumina-based composite sol composition is 1.6 mass % to 6.8 mass %.
[0019] (3) The alumina-based composite sol composition described in (1) or (2) above, wherein the (C) polybasic organic acid is at least one selected from itaconic acid, citric acid, glutaric acid, succinic acid, citraconic acid, maleic acid, malonic acid, or malic acid.
[0020] (4) The alumina-based composite sol composition according to any one of (1) to (3) above, wherein (A) the alumina sol containing alumina hydrate is an alumina sol obtained by hydrolysis of an aluminum alkoxide.
[0021] (5) The alumina-based composite sol composition according to any one of (1) to (4) above, wherein the alumina hydrate is a scaly alumina hydrate particle having a short diameter of 5 to 15 nm and a long diameter of 10 to 50 nm.
[0022] (6) The alumina-based composite sol composition according to any one of (1) to (5) above, wherein the alumina hydrate has at least one crystal form selected from the group consisting of amorphous, boehmite, and pseudo-boehmite.
[0023] (7) The alumina-based composite sol composition according to any one of (1) to (6) above, wherein the alkoxysilane compound (B) is represented by the following general formula (1):
[0024] R 1 n (R 3 ) m Si(OR 2 ) 4-m-n (1)
[0025] (Where R 1 represents a group containing an epoxy group or a (meth)acryloyl group, R 2 and R 3 represents an alkyl group having 1 to 4 carbon atoms, wherein n is in the range of 0 to 2, m is in the range of 0 to 3, and n+m is in the range of 0 to 3. ).
[0026] (8) The alumina-based composite sol composition according to any one of (1) to (7) above, wherein the solvent (D) is water, alcohol, or a combination of water and alcohol.
[0027] (9) The alumina-based composite sol composition according to any one of (1) to (8) above, wherein the amount of the alkoxysilane compound (B) is 105 to 460 parts by mass based on 100 parts by mass of the alumina hydrate.
[0028] (10) The alumina-based composite sol composition according to any one of (1) to (9) above, wherein the amount of the polybasic organic acid (C) is 1 to 20 parts by mass based on 100 parts by mass of the solid content in the alumina-based composite sol composition.
[0029] (11) The alumina-based composite sol composition according to any one of (1) to (10) above, which is a coating composition.
[0030] (12) The alumina-based composite sol composition according to any one of (1) to (11) above, which is an insulating coating agent or a hard coating agent.
[0031] A second embodiment of the present invention is the following method for producing an alumina-based composite sol composition.
[0032] (13) A method for producing an alumina-based composite sol composition, comprising mixing (A) an alumina sol containing alumina hydrate, (B) an alkoxysilane compound, (C) a polybasic organic acid, and (D) a solvent, wherein the amount of alumina hydrate in the (A) alumina sol is 3% by mass to 11% by mass.
[0033] (14) A method for producing an alumina-based composite sol composition, comprising mixing (A) an alumina sol containing alumina hydrate, (B) an alkoxysilane compound, (C) a polybasic organic acid, and (D) a solvent, wherein the amount of alumina hydrate in the alumina-based composite sol composition is 1.6 mass % to 6.8 mass %.
[0034] (15) A method for producing an alumina-based composite sol composition according to (13) or (14) above, wherein (C) the polybasic organic acid is at least one selected from itaconic acid, citric acid, glutaric acid, succinic acid, citraconic acid, maleic acid, malonic acid, or malic acid.
[0035] (16) The method for producing an alumina-based composite sol composition according to any one of (13) to (15) above, wherein (A) the alumina sol containing alumina hydrate is an alumina sol obtained by hydrolysis of an aluminum alkoxide.
[0036] (17) The method for producing an alumina-based composite sol composition according to any one of (13) to (16) above, wherein the alumina hydrate is a scaly alumina hydrate particle having a short diameter of 5 to 15 nm and a long diameter of 10 to 50 nm.
[0037] (18) The method for producing an alumina-based composite sol composition according to any one of (13) to (17), wherein the alumina hydrate has at least one crystal form selected from the group consisting of amorphous, boehmite, and pseudo-boehmite.
[0038] (19) The method for producing an alumina-based composite sol composition according to any one of (13) to (18), wherein the alkoxysilane compound (B) is represented by the following general formula (1):
[0039] R 1 n (R 3 ) m Si(OR 2 ) 4-m-n (1)
[0040] (In the above formula, R 1 represents a group containing an epoxy group or a (meth)acryloyl group, R 2 and R 3 represents an alkyl group having 1 to 4 carbon atoms, wherein n is in the range of 0 to 2, m is in the range of 0 to 3, and n+m is in the range of 0 to 3. ).
[0041] (20) The method for producing an alumina-based composite sol composition according to any one of (13) to (19) above, wherein the solvent (D) is water, alcohol, or a combination of water and alcohol.
[0042] (21) The method for producing an alumina-based composite sol composition according to any one of (13) to (20) above, wherein the amount of the alkoxysilane compound (B) is 105 to 460 parts by mass based on 100 parts by mass of the alumina hydrate.
[0043] (22) A method for producing an alumina-based composite sol composition according to any one of (13) to (21) above, wherein the amount of (C) the polybasic organic acid is 1 to 20 parts by mass relative to 100 parts by mass of the total amount of the alumina hydrate in the (A) alumina sol and the (B) alkoxysilane compound.
[0044] A third embodiment of the present invention is a method for producing an alumina-based composite thin film, comprising applying the alumina-based composite sol composition described in any one of (1) to (12) above to a substrate surface and curing the composition.
[0045] A fourth embodiment of the present invention is an alumina sol including scaly alumina hydrate particles defined by a short diameter of 5 to 15 nm and a long diameter of 10 to 50 nm.
[0046] The fifth embodiment of the present invention is a method for producing alumina sol according to the fourth embodiment of the present invention, comprising: (1) stirring aluminum alkoxide in water at a temperature of 70° C. to 100° C. in the absence of an acid;
[0047] (2) A step of adding an acid to the reaction solution obtained in the above step (1) and stirring the mixture.
[0048] Effects of the Invention
[0049] According to the first embodiment of the present invention, an alumina-based composite sol composition can be obtained, which can be used to produce an alumina-based composite thin film having high insulation and hardness, excellent adhesion to a substrate, and applicable to various substrates by heat treatment at a relatively low temperature using a sol-gel method. In addition, according to the second embodiment of the present invention, an alumina-based composite sol composition can be produced, which can be used to produce an alumina-based composite thin film having high insulation and hardness, excellent adhesion to a substrate, and applicable to various substrates by heat treatment at a relatively low temperature using a sol-gel method.
[0050] According to the third embodiment of the present invention, an aluminum oxide-based composite thin film having high insulation and hardness, excellent adhesion to a substrate, and applicable to various substrates can be produced by heat treatment at a relatively low temperature using a sol-gel method.
[0051] In addition, according to the fourth embodiment of the present invention, an alumina sol suitable for the production of an alumina-based composite sol composition can be obtained, the composition can be used to produce an alumina-based composite thin film having high insulation and hardness, excellent adhesion to a substrate, and applicable to various substrates by heat treatment at a relatively low temperature by a sol-gel method. In addition, according to the fifth embodiment of the present invention, an alumina sol suitable for the production of an alumina-based composite sol composition can be produced, the composition can be used to produce an alumina-based composite thin film having high insulation and hardness, excellent adhesion to a substrate, and applicable to various substrates by heat treatment at a relatively low temperature by a sol-gel method. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is a photograph of an aluminum oxide composite thin film formed on an aluminum substrate.
[0053] Figure 2 This is a transmission electron microscope (TEM) photograph of alumina sol. DETAILED DESCRIPTION
[0054] [Alumina-based composite sol composition and method for producing the same]
[0055] The alumina composite sol composition as the first embodiment of the present invention contains (A) an alumina sol containing an alumina hydrate, (B) an alkoxysilane compound, (C) a polybasic organic acid, and (D) a solvent. Here, the amount of the alumina hydrate in the (A) alumina sol is 3% to 11% by mass. Alternatively, the amount of the alumina hydrate in the alumina composite sol composition is 1.6% to 6.8% by mass.
[0056] According to this embodiment, an alumina-based composite sol composition can be obtained which can produce an alumina-based composite thin film having high insulation and hardness, excellent adhesion to a substrate, and applicable to various substrates by heat treatment at a relatively low temperature using a sol-gel method.
[0057] (A) Alumina sol
[0058] The alumina-based composite sol composition contains (A) an alumina sol containing alumina hydrate. The so-called alumina sol is a colloidal solution in which particles of alumina hydrate are dispersed in a dispersion medium such as water and alcohol. When the dispersion medium is water, the composition of the colloid is formally represented by Al2O3·nH2O. There are various methods for preparing alumina sols, and the morphology and crystallinity of the particles of alumina hydrate vary depending on the manufacturing methods and manufacturing conditions. It should be noted that the so-called "alumina" is synonymous with "alumina" whose composition formula is represented by Al2O3.
[0059] In this embodiment, the amount of alumina hydrate in (A) alumina sol is 3% to 11% by mass, preferably 3% to 9% by mass, and more preferably 3% to 5% by mass. By setting the amount of alumina hydrate in alumina sol to 3% or more by mass, the viscosity of the alumina composite sol composition can be appropriately increased, the coating property of the alumina composite sol composition can be improved, and the insulation property can be improved. By setting the amount of alumina hydrate in alumina sol to 11% or less by mass, the viscosity of the alumina composite sol composition can be prevented from being too high, the coating property of the coating composition can be improved, and the dielectric breakdown strength can be improved. Here, the amount of alumina hydrate in the so-called alumina sol is equivalent to the amount of material charged when the composition is manufactured.
[0060] Alternatively, in the present embodiment, the amount of alumina hydrate in the alumina composite sol composition is 1.6 mass% to 6.8 mass%, preferably 1.6 mass% to 5.5 mass%, and more preferably 1.8 mass% to 4.5 mass%. By setting the amount of alumina hydrate in the alumina composite sol composition to 1.6 mass% or more, the viscosity of the alumina composite sol composition can be appropriately increased, the coating property of the alumina composite sol composition can be improved, and the insulation property can be improved. By setting the amount of alumina hydrate in the alumina composite sol composition to 6.8 mass% or less, the viscosity of the alumina composite sol composition can be prevented from being too high, the coating property of the coating composition can be improved, and the dielectric breakdown strength can be improved. Here, the amount of alumina hydrate in the alumina composite sol composition is equivalent to the amount of material charged when the composition is manufactured.
[0061] Alumina sol can be produced by wet methods such as sol-gel method, and its production methods are complicated and diverse. The so-called sol-gel method is a method in which metal organic compounds such as metal alkoxides, metal acetylacetonates, metal carboxylates, and metal inorganic compounds such as nitrates, chlorides, and sulfates are hydrolyzed and dehydrated and polycondensed in a solution to obtain a sol in which metal oxides or metal hydroxides are dispersed, and the reaction is further promoted to gel (solidify) to produce an oxide solid. As such a method, various methods are exemplified, such as a method of hydrolyzing an aluminum alkoxide (BEYoldas, Amer. Ceram. Soc. Bull. 54, 289 (1975) etc.), a method of hydrothermally treating an alumina gel obtained by neutralizing a water-soluble basic aluminum salt with a base in the presence of an organic acid (Japanese Patent Application Laid-Open Nos. 53-112299 and 54-116398), a method of hydrothermally treating an alumina gel obtained by liquid phase neutralization reaction of an acidic aluminum compound with an alkaline substance in the presence of a monobasic inorganic acid (Japanese Patent Application Laid-Open No. 55-27824), and a method of neutralizing an aqueous solution of an alkali metal aluminate with an aqueous solution of an organic hydroxy acid (Japanese Patent Application Laid-Open No. 59-223223). In the present embodiment, the alumina sol is preferably an alumina sol obtained by hydrolyzing an aluminum alkoxide from the viewpoint of obtaining amorphous, boehmite or pseudo-boehmite type alumina.
[0062] Among the alumina hydrate particles contained in the alumina sol, there are particles of various shapes such as plate-like, columnar, needle-like, particle-like, and fibrous. The physical properties of the alumina sol vary depending on the shape of the alumina hydrate particles, and the uses vary depending on the physical properties. In the present embodiment, from the viewpoint of producing a dense thin film with high insulation and hardness, the alumina hydrate in (A) the alumina sol is preferably a scaly alumina hydrate particle defined by a short diameter of 5 to 15 nm and a long diameter of 10 to 50 nm. The alumina sol containing scaly alumina hydrate particles defined by a short diameter of 5 to 15 nm and a long diameter of 10 to 50 nm is the fourth embodiment of the present invention. In this specification, the particle size of the alumina hydrate particles adopts the value obtained using a transmission electron microscope (TEM).
[0063] It is known that there are many crystal forms of aluminum oxide, such as amorphous, boehmite, pseudo-boehmite, γ-alumina, θ-alumina and α-alumina. In the present embodiment, from the viewpoint of the insulation of the aluminum oxide composite film, the aluminum oxide hydrate in (A) the aluminum oxide sol preferably has at least one crystal form selected from amorphous, boehmite and pseudo-boehmite. The crystal form of the aluminum oxide hydrate in the aluminum oxide sol can be prepared, for example, by adjusting the type of aluminum alkoxide described later, its hydrolysis conditions or degumming conditions. Here, the crystal form of the aluminum oxide hydrate in the aluminum oxide sol can be confirmed under the following conditions using an X-ray diffraction apparatus (e.g., trade name "Ultima IV", manufactured by RIGAKU Co., Ltd.). In the present embodiment, amorphous or low-crystalline boehmite or pseudo-boehmite is preferred, in which case the X-ray diffraction shows a broad spectrum.
[0064] <Conditions> Tubular bulb: Cu, tube voltage: 40kV, tube current: 40mA, sampling width: 0.020°, scanning speed: 20° / min, divergence slit: 2 / 3°, divergence longitudinal limiting slit: 10mm, scattering slit: 13mm, light receiving slit: 13mm.
[0065] Alumina sol containing scaly alumina hydrate particles having a short diameter of 5 to 15 nm and a long diameter of 10 to 50 nm can be produced, for example, by a method comprising the steps of (1) stirring an aluminum alkoxide in water at a temperature of 70° C. to 100° C. in the absence of an acid, and (2) adding an acid to the reaction solution obtained in the step (1) and stirring. This method for producing alumina sol is a fifth embodiment of the present invention.
[0066] In the above step (1), the aluminum alkoxide in water is stirred at a temperature of 70°C to 100°C in the absence of an acid. By stirring at a temperature of 70°C to 100°C, a sol in which aluminum oxide hydrate is dispersed in a solution is formed through a hydrolysis reaction and a polycondensation reaction of the aluminum alkoxide in water. The stirring can be performed in any atmosphere of an air atmosphere or an inert gas atmosphere such as nitrogen, argon, etc., but is preferably performed in an inert gas atmosphere such as nitrogen, argon, etc. The stirring in step (1) is performed at a temperature of 70°C to 100°C, preferably at a temperature of 80°C to 90°C. The stirring time in step (1) can vary depending on conditions such as the stirring temperature, and is, for example, 1 minute to 1 hour.
[0067] Specific examples of the aluminum alkoxide include aluminum ethoxide, aluminum n-butoxide, aluminum sec-butoxide, aluminum tert-butoxide, and aluminum isopropoxide.
[0068] In the present specification, aluminum alkoxide also includes aluminum chelate compounds. Specific examples of such aluminum chelate compounds include cyclic aluminum oligomers, (ethyl acetoacetate) diisopropoxyaluminum, and tris(ethyl acetoacetate) aluminum.
[0069] Among these compounds, compounds having an alkoxy group having 2 to 5 carbon atoms are preferred because they have moderate hydrolyzability and are easy to remove by-products.
[0070] In the above step (1), the solid content concentration of the aluminum alkoxide in water is preferably 9 to 18% by mass, and more preferably 9 to 12% by mass. By making the solid content concentration 9% or more, the obtained alumina hydrate particles can be uniformly sized. On the other hand, by making the solid content concentration 18% or less, the stirring property of the reaction solution can be well maintained.
[0071] Then, an acid is added to the reaction solution obtained in the above step (1), and the mixture is stirred (step (2)). In the step (2), the condensed solid is dispersed in the solution again due to the action of the acid to form a colloid (decolloidation). Thus, a sol in which aluminum oxide hydrate is dispersed in the solution can be formed. It should be noted that in the step (2), a hydrolysis reaction and a polycondensation reaction of the unreacted aluminum alkoxide may also occur simultaneously.
[0072] The formation process of the sol is based on the competitive reaction between the hydrolysis reaction of the alkoxide group and the polycondensation reaction by the Al-OH group. Therefore, the reaction rate ratio of the polycondensation reaction to the hydrolysis reaction becomes an important factor. In the conventional method for producing alumina sol by hydrolyzing aluminum alkoxide, the aluminum alkoxide in water is stirred in the presence of an acid from the beginning for hydrolysis. In the present embodiment, step (1) is carried out in the absence of an acid, and an acid is added in step (2), thereby controlling the reaction rate ratio of the polycondensation reaction to the hydrolysis reaction, thereby controlling the structure of the sol.
[0073] The acid used in the above step (2) is preferably a monobasic acid, for example, inorganic acids such as nitric acid and hydrochloric acid, and organic acids such as formic acid, acetic acid, propionic acid, and butyric acid. Organic acids are preferred because they are less likely to affect the properties of the resulting film and because of operability. As an organic acid, acetic acid is preferred from the perspective of operability and economy. The amount of the acid used is preferably 0.05 to 0.2 molar times, more preferably 0.1 to 0.16 molar times, relative to the aluminum alkoxide.
[0074] The stirring in step (2) is performed at, for example, 70 to 100° C., preferably 80 to 90° C. The stirring in step (2) may vary depending on the stirring conditions, and may be performed for, for example, 50 to 150 hours, preferably 70 to 120 hours.
[0075] In the steps (1) and (2), alcohol is generated as a by-product by the hydrolysis reaction of the aluminum alkoxide. The alcohol may be removed from the reaction system by distillation, or need not be removed by distillation.
[0076] After step (2), the reaction solution is cooled to room temperature as necessary, and the supernatant of the reaction solution is collected by centrifugation or the like, thereby obtaining an alumina sol.
[0077] (B) Alkoxysilane compound
[0078] The alumina composite sol composition includes (B) an alkoxysilane compound. In this specification, (B) an alkoxysilane compound refers to a compound having one or more alkoxy groups on silicon. In this embodiment, (B) an alkoxysilane compound is preferably a compound represented by the following general formula (1):
[0079] R 1 n (R 3 ) m Si(OR 2 ) 4-m-n (1)
[0080] (In the above formula, R 1 represents a group containing an epoxy group or a (meth)acryloyl group, R 2 and R 3 represents an alkyl group having 1 to 4 carbon atoms, wherein n is in the range of 0 to 2, m is in the range of 0 to 3, and n+m is in the range of 0 to 3. ).
[0081] The sol composition finally obtained contains (B) an alkoxysilane compound, and it can be considered that, although its specific structure is not certain, the alumina hydrate in the (A) alumina sol is bonded to the silanol group generated by hydrolyzing a part of the (B) alkoxysilane compound to generate an alumina hydrate-alkoxysilane compound complex (also referred to as an alumina-based complex in this specification), and a sol in which the complex is dispersed in a solution is formed. That is, the alumina-based composite sol composition is a colloidal solution in which particles of the alumina-based composite are dispersed in a dispersion medium. However, a part of the (B) alkoxysilane compound is not hydrolyzed and remains in the solution, and the alumina hydrate particles in the (A) alumina sol that are not bonded to the silanol group also exist in the solution. Therefore, in the alumina-based composite sol composition, the alumina-based composite, the alumina hydrate and the alkoxysilane compound are contained as solid components.
[0082] The amount of the alkoxysilane compound (B) is preferably 105 to 460 parts by mass, more preferably 150 to 450 parts by mass, and even more preferably 250 to 400 parts by mass, relative to 100 parts by mass of the alumina hydrate in the alumina sol (A). Here, the amount of the alkoxysilane compound (B) corresponds to the amount charged when mixed with the alumina sol (A).
[0083] Specific examples of alkoxysilane compounds include so-called silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, and 3-acryloxypropyltrimethoxysilane. In addition, tetraethoxysilane (TEOS) can be mentioned. Other specific examples of the alkoxysilane compound include vinyl trimethoxysilane, vinyl triethoxysilane, p-phenylene trimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyl trimethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl- Silane coupling agents such as butylene) propylamine, N-phenyl-3-aminopropyl trimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyl trimethoxysilane, tris(trimethoxysilylpropyl) isocyanurate, 3-ureapropyl trialkoxysilane, 3-mercaptopropyl methyl dimethoxysilane, 3-mercaptopropyl trimethoxysilane, 3-isocyanate propyl triethoxysilane, 3-trimethoxysilylpropyl succinic anhydride. Alkoxysilane compounds can be appropriately selected according to the type of substrate as the coating object. They can be used alone or in combination of two or more.
[0084] (C) Polybasic organic acid
[0085] The alumina composite sol composition contains (C) a polybasic organic acid. In this specification, the so-called polybasic organic acid refers to a compound having two or more carboxyl groups or sulfonic groups in one molecule, preferably a compound having two or more carboxyl groups in one molecule, and more preferably a compound having two carboxyl groups in one molecule. By containing (C) a polybasic organic acid, the particles of the alumina composite sol are cross-linked within and / or between particles, so that the alumina composite sol particles are stabilized. In addition, by containing (C) a polybasic organic acid, a composite body of alumina hydrate, alkoxysilane compound and polybasic organic acid cross-linked is formed in the alumina composite film obtained as a result, and an alumina composite film having a dense structure, high insulation and hardness can be formed.
[0086] As the polybasic organic acid, for example, oxalic acid, itaconic acid, citric acid, glutaric acid, succinic acid, citraconic acid, maleic acid, malonic acid, malic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, trimesic acid, aconitic acid, oxaloacetic acid, etc. can be mentioned, preferably itaconic acid, citric acid, glutaric acid, succinic acid, citraconic acid, maleic acid, malonic acid, or malic acid. These can be used alone or in combination of two or more.
[0087] The polybasic organic acid may be in the form of a salt. Examples of the polybasic organic acid salt include alkali metal salts, alkaline earth metal salts, ammonium salts, and amine salts. Among them, from the viewpoint of improving the solubility of the polybasic organic acid in water, alkali metal salts or ammonium salts are preferred, and sodium salts, potassium salts, or ammonium salts are more preferred.
[0088] The amount of the polybasic organic acid (C) is preferably 1 to 20 parts by mass, and more preferably 2 to 15 parts by mass, relative to 100 parts by mass of the total amount of the alumina hydrate in the (A) alumina sol and the amount of the alkoxysilane compound (B). Alternatively, the amount of the polybasic organic acid (C) is preferably 1 to 20 parts by mass, and more preferably 2 to 15 parts by mass, relative to 100 parts by mass of the solid content in the alumina composite sol composition. The amount of the polybasic organic acid (C) corresponds to the amount of material charged when the composition is produced.
[0089] (D) Solvent
[0090] The alumina-based composite sol composition contains (D) a solvent. As the solvent, water, alcohol such as methanol, ethanol, propanol, or a combination of water and alcohol can be used, and water, ethanol, or a combination of water and ethanol is preferred.
[0091] The alumina-based composite sol composition may contain additives such as a curing agent, a viscosity adjuster, a pH adjuster, and a coloring component, as long as they do not adversely affect the performance.
[0092] In one embodiment, the solid content in the alumina composite sol composition is preferably in the range of 6.5 to 15% by mass. By making the solid content 6.5% by mass or more, the film thickness per coating is sufficient. On the other hand, by making the total solid content 15% by mass or less, the operability during film formation and the stability of the coating liquid can be obtained. The so-called solid content in the alumina composite sol composition includes the alumina composite, alumina hydrate and alkoxysilane compound present in the alumina composite sol composition.
[0093] The amount of the solvent (D) is preferably adjusted so that the amount of alumina hydrate in the alumina composite sol composition is 1.6 mass % to 6.8 mass %. In addition, the amount of the solvent (D) is preferably adjusted so that the solid content in the alumina composite sol composition is in the range of 6.5 mass % to 15 mass %.
[0094] In one embodiment, the viscosity of the alumina composite sol composition is preferably 14 to 22 mPa·s. When the viscosity is within this range, the film thickness per coating is sufficient, and workability during film formation and stability of the coating liquid can be achieved.
[0095] The alumina composite sol composition can be prepared by mixing (A) an alumina sol containing an alumina hydrate, (B) an alkoxysilane compound, (C) a polybasic organic acid, and (D) a solvent. Here, the amount of alumina hydrate in the (A) alumina sol is 3% to 11% by mass. Alternatively, the amount of alumina hydrate in the alumina composite sol composition is 1.6% to 6.8% by mass. The method for preparing the alumina composite sol composition is a second embodiment of the present invention. As a method for mixing, these components can be mixed at once, or, for example, (A) an alumina sol and (D) a solvent can be mixed to obtain a first mixed solution, and on the other hand, (B) an alkoxysilane compound, (C) a polybasic organic acid, and (D) a solvent can be mixed to obtain a second mixed solution, and then these first mixed solutions and second mixed solutions can be mixed.
[0096] The mixing of these components can be performed at a temperature of, for example, 10° C. to 100° C., preferably at room temperature. The mixing time of these components can vary depending on the mixing temperature, and is, for example, 1 to 200 hours, preferably 50 to 120 hours.
[0097] Alumina composite sol compositions can be used as coating compositions. In particular, since alumina composite films having high insulation and hardness, excellent adhesion to substrates, and applicable to various substrates can be produced at relatively low temperatures by the sol-gel method, they can be used as insulating coating agents or hard coating agents. When used as insulating coating agents, for example, they can be applied to metal substrates such as iron, copper, aluminum, titanium, steel, stainless steel (SUS), and brass; ceramic substrates such as Al2O3, SiO2, ZrO, TiO2, glass, tiles, and pottery; organic substrates such as carbon, graphite, paper, wood chips, polyvinyl alcohol, polypropylene, polycarbonate, polyimide, polyethylene terephthalate, acrylic resins, polyurethanes, and other plastics; and substrates such as magnetic materials. When used as a hard coating agent, it can be applied to metal substrates such as iron, copper, aluminum, titanium, steel, stainless steel (SUS), brass, etc.; ceramic substrates such as Al2O3, SiO2, ZrO, TiO2, glass, tiles, pottery, etc.; organic substrates such as carbon, graphite, paper, wood chips, polyvinyl alcohol, polypropylene, polycarbonate, polyimide, polyethylene terephthalate, acrylic resin, polyurethane, etc.; substrates such as magnetic materials. More specifically, it can be used for insulating coatings or hard coatings on the inner surface of a device (aluminum, SUS, etc.), insulating coatings or hard coatings on winding coils (Cu, etc.), insulating coatings or hard coatings on flexible substrates (polyimide, polyethylene terephthalate, etc.), insulating coatings or hard coatings on magnetic bodies, insulating coatings of metal powders or carbon powders, insulating coatings or hard coatings on electronic components, and insulating coatings or hard coatings on ceramics such as glass and silica.
[0098] In addition, the alumina-based composite sol composition can be used as a sealing agent, for example, for sealing the pores of thermal sprayed films (metals, ceramics) and porous materials.
[0099] [Method for producing alumina-based composite thin film]
[0100] The method for producing an aluminum oxide-based composite thin film according to the present embodiment includes applying the aluminum oxide-based composite sol composition according to the first embodiment to a substrate surface and curing the composition.
[0101] There is no limitation on the type and shape of the substrate to which the alumina-based composite sol composition is applied, and examples thereof include metal substrates such as iron, copper, aluminum, titanium, steel, stainless steel (SUS), and brass; ceramic substrates such as Al2O3, SiO2, ZrO, TiO2, glass, tiles, and pottery; organic substrates such as plastics such as carbon, graphite, paper, wood chips, polyvinyl alcohol, polypropylene, polycarbonate, polyimide, polyethylene terephthalate, acrylic resins, and polyurethane; and substrates such as magnetic materials.
[0102] As a method for applying the alumina-based composite sol composition, a dipping method, a spin coating method, a spray method, a jet dispensing method, a screen printing method, a laminar flow method, an electrophoresis method, etc. can be appropriately selected according to the type of substrate.
[0103] After the alumina-based composite sol composition is applied to the surface of the substrate, it is cured by heat treatment to form an alumina-based composite film. The temperature of the heat treatment is, for example, 80°C to 230°C, preferably 110°C to 200°C. The time of the heat treatment can vary depending on the temperature of the heat treatment, for example, 5 minutes to 60 minutes. The alumina-based composite sol composition of the first embodiment does not need to be heat treated at a temperature of 500°C or more, which is required for the sintering of the metal oxide, and can therefore be applied to various substrates. In addition, the alumina-based composite sol composition of the first embodiment can form an alumina-based composite film having a dense structure, high insulation and hardness even by heat treatment at a relatively low temperature.
[0104] Although the specific structure of the aluminum oxide composite film is unknown, it is believed that the aluminum oxide composite film is a composite cross-linked with aluminum oxide hydrate, alkoxysilane compound and polybasic organic acid, and has a dense and strong structure. As a result, the aluminum oxide composite film exhibits high insulation and hardness.
[0105] The thickness of the aluminum oxide composite film can be appropriately selected according to the application, for example, 0.01 μm to 30 μm, preferably 0.1 μm to 10 μm, and more preferably 1 μm to 5 μm. By making the film thickness within the above range, the desired insulation and hardness can be obtained, and the generation of cracks during heat treatment can be avoided.
[0106] Example
[0107] Hereinafter, the present invention will be described in further detail using Examples and Comparative Examples; however, the present invention is not limited to these Examples.
[0108] [Manufacturing of Alumina Sol]
[0109] Preparation Example 1 Preparation of Alumina Sol A
[0110] To a 50 L reaction container, add 43880 g of pure water and 4570 g of aluminum isopropoxide, raise the liquid temperature to 85°C while stirring, and stir for 10 minutes. Add 1550 g of aqueous acetic acid solution (210 g of acetic acid) to the reaction liquid, and react at 85°C for 72 to 120 hours. Cool the reaction liquid to room temperature to terminate the reaction. While confirming the particle size of the reaction liquid using a laser diffraction / scattering particle size distribution measuring device (LA-960, manufactured by Horiba, Ltd.), centrifuge the reaction liquid and collect the supernatant to obtain alumina sol A. The obtained alumina sol A was observed using a transmission electron microscope (TEM) (HT7700, manufactured by Hitachi High-Tech Co., Ltd. (100 kV)), and the results are as follows. Figure 2 As shown, the sol is a sol in which scaly alumina hydrate particles having a short diameter of 5 to 15 nm and a long diameter of 10 to 50 nm are dispersed. The concentration of alumina hydrate in the alumina sol is 3% by mass.
[0111] Preparation Example 2 Preparation of Alumina Sol B
[0112] The procedure of Preparation Example 1 was repeated except that pure water was changed to 43380 g and aluminum isopropoxide was changed to 5070 g, thereby obtaining an alumina sol B in which scaly alumina hydrate particles having a short diameter of 5 to 15 nm and a long diameter of 10 to 50 nm were dispersed. The alumina hydrate concentration in the alumina sol was 4 mass %.
[0113] Preparation Example 3 Preparation of Alumina Sol C
[0114] The procedure of Preparation Example 1 was repeated except that pure water was changed to 39880 g and aluminum isopropoxide was changed to 8570 g, thereby obtaining an alumina sol C in which scaly alumina hydrate particles having a short diameter of 5 to 15 nm and a long diameter of 10 to 50 nm were dispersed. The alumina hydrate concentration in the alumina sol was 11 mass %.
[0115] Preparation Example 4 Preparation of Alumina Sol D
[0116] The procedure of Preparation Example 1 was repeated except that pure water was changed to 44130 g and aluminum isopropoxide was changed to 4320 g, thereby obtaining an alumina sol D in which scaly alumina hydrate particles having a short diameter of 5 to 15 nm and a long diameter of 10 to 50 nm were dispersed. The alumina hydrate concentration in the alumina sol was 2.5 mass %.
[0117] Preparation Example 5 Preparation of Alumina Sol E
[0118] The procedure of Preparation Example 1 was repeated except that pure water was changed to 39630 g and aluminum isopropoxide was changed to 8820 g, thereby obtaining an alumina sol E in which scaly alumina hydrate particles having a short diameter of 5 to 15 nm and a long diameter of 10 to 50 nm were dispersed. The alumina hydrate concentration in the alumina sol was 11.5 mass %.
[0119] [Production of Alumina-Based Composite Sol Composition]
[0120] (Examples 1 to 14 and Comparative Examples 1 to 3)
[0121] The raw materials and feed amounts (parts by mass) described in Table 1 were used. Alumina sol and pure water were added to a 50 L reaction container, and stirred at room temperature for 60 minutes to obtain reaction solution A. On the other hand, an alkoxysilane compound was mixed with an organic acid solution containing a polybasic organic acid and water, and stirred at room temperature for 1 hour to obtain reaction solution B. Reaction solution B was added to reaction solution A, and the mixture was stirred at room temperature for 96 hours to obtain alumina composite sol compositions of Examples 1 to 14 and Comparative Examples 1 to 2. In Comparative Example 3, the alumina composite sol composition of Comparative Example 3 was obtained in the same manner as in Example 1 except that the polybasic organic acid was not included.
[0122] In the table, the (B) alkoxysilane compounds used are shown below.
[0123] (B) Alkoxysilane compound A: 3-glycidoxypropyltrimethoxysilane
[0124] [Chemistry 1]
[0125]
[0126] (B) Alkoxysilane compound B: 3-glycidoxypropyltriethoxysilane
[0127] [Chemistry 2]
[0128]
[0129] [Viscosity measurement]
[0130] The viscosity of the alumina-based composite sol compositions of Examples and Comparative Examples was measured using a Brookfield viscometer DV2TCP (cone and plate: CPA-52Z, rotation speed: 200 rpm).
[0131] [Manufacturing of Alumina-based Composite Thin Films]
[0132] The alumina composite sol composition of the embodiment and the comparative example was coated on an aluminum substrate (substrate) by an immersion method and heated at 150° C. for 1 hour to obtain an alumina composite thin film on the aluminum substrate. Figure 1 The film thickness of the aluminum oxide composite film was measured using an electromagnetic-eddy current type small film thickness measuring instrument DUAL SCOPE FMP40 (manufactured by Fischer Instruments). The results are shown in Table 1.
[0133] [Dielectric breakdown strength]
[0134] The alumina composite sol composition of the embodiment and the comparative example was coated on an aluminum substrate (substrate) by an immersion method and heated at 150°C for 1 hour to obtain an alumina composite film on the aluminum substrate. The alumina composite film on the aluminum substrate was used to measure the insulation breakdown voltage using a withstand voltage tester DAC-6041 (manufactured by Soken Electric Co., Ltd.) and calculate the insulation breakdown strength. The results are shown in Table 1. When the insulation breakdown strength is 200V / umm or more, the insulation breakdown strength is high and is considered good.
[0135] [Adhesion 1]
[0136] The alumina composite sol composition of the embodiment and the comparative example was coated on an aluminum substrate (substrate) by an immersion method, and heated at 150° C. for 1 hour to obtain an alumina composite thin film on the aluminum substrate. The alumina composite thin film on the aluminum substrate was evaluated for adhesion by the method specified in JIS K 5600-5-6. The results are shown in Table 1. When the evaluation of adhesion is 1 or less, the adhesion is high and is considered good.
[0137] [Hardness (pencil hardness)]
[0138] The alumina composite sol composition of the embodiment and the comparative example was coated on an aluminum substrate (substrate) by an immersion method, and heated at 150° C. for 1 hour to obtain an alumina composite thin film on the aluminum substrate. The alumina composite thin film on the aluminum substrate was tested for the hardness of the coating film by the pencil hardness test specified in JIS K 5600-5-4. The results are shown in Table 1. When the pencil hardness is 6H or more, the hardness is high and is considered good.
[0139] [Insulation resistance]
[0140] The alumina composite sol composition of the embodiment and the comparative example was coated on an aluminum substrate (substrate) by an immersion method, and heated at 150°C for 1 hour to obtain an alumina composite film on the aluminum substrate. Electrodes were arranged on the alumina composite film portion, and the insulation resistance value when a voltage of 100V was applied was measured using a superinsulator SM-8220 (manufactured by Hioki Electric Co., Ltd.). The results are shown in Table 1. When the insulation resistance value is 1.0E+11Ω or more, the insulation is high and is considered good.
[0141] [Table 1-1]
[0142]
[0143] [Table 1-2]
[0144]
[0145] [Table 1-3]
[0146]
[0147] From the results shown in Table 1, it can be seen that by using the alumina-based composite sol compositions of Examples 1 to 14, an alumina-based composite thin film having high insulation, dielectric breakdown strength, adhesion, and hardness can be produced. On the other hand, the alumina-based composite thin film produced using the alumina-based composite sol composition of Comparative Example 1 cannot obtain sufficient insulation. The alumina-based composite thin film produced using the alumina-based composite sol composition of Comparative Example 2 cannot obtain sufficient dielectric breakdown strength. For the alumina-based composite sol composition of Comparative Example 3, a film having a sufficient film thickness cannot be produced, and the measurements of insulation, dielectric breakdown strength, adhesion, and hardness cannot be completed.
[0148] [Adhesion 2]
[0149] The alumina composite sol composition of Example 2 was coated on an aluminum substrate, an alumina substrate, a glass substrate, and a polyimide substrate by an immersion method, and heated at 150°C for 1 hour to obtain an alumina composite film on each substrate. The alumina composite film on each substrate was evaluated for adhesion by the method specified in JIS K 5600-5-6. The results are shown in Table 2. When the evaluation of adhesion is 1 or less, the adhesion is high and is considered good. As can be seen from the results shown in Table 2, adhesion is good in all substrates.
[0150] [Table 2]
[0151] Aluminum substrate Alumina substrate Glass substrate Polyimide substrate Adhesion 0 0 0 0
[0152] The entire contents of the disclosure of Japanese Patent Application No. 2020-203873 (filing date: December 9, 2020) are incorporated into this specification by reference.
[0153] All documents, patent applications, and technical standards described in this specification are incorporated herein by reference to the same extent as if each individual document, patent application, or technical standard was specifically and individually indicated to be incorporated by reference.
[0154] Description of Reference Numerals
[0155] 1 Coating part
[0156] 2 Uncoated part (aluminum substrate)
Claims
1. An alumina-based composite sol composition comprising an alumina sol A containing an alumina hydrate, an alkoxysilane compound B, a polybasic organic acid C and a solvent D, The amount of alumina hydrate in the alumina sol A is 3% to 9% by mass, and the alumina hydrate is scaly alumina hydrate particles having a short diameter of 5 nm to 15 nm and a long diameter of 10 nm to 50 nm. The polybasic organic acid C is at least one selected from itaconic acid, citric acid, glutaric acid, succinic acid, citraconic acid, maleic acid, malonic acid, malic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, trimesic acid, aconitic acid, and oxaloacetic acid, The amount of the alkoxysilane compound B is 105 to 460 parts by mass based on 100 parts by mass of the alumina hydrate. The amount of the polybasic organic acid C is 1 to 20 parts by mass based on 100 parts by mass of the solid content in the alumina-based composite sol composition.
2. An alumina-based composite sol composition comprising an alumina sol A containing an alumina hydrate, an alkoxysilane compound B, a polybasic organic acid C and a solvent D, The amount of alumina hydrate in the alumina-based composite sol composition is 1.6 mass % to 5.5 mass %, and the alumina hydrate is scaly alumina hydrate particles having a short diameter of 5 nm to 15 nm and a long diameter of 10 nm to 50 nm. The polybasic organic acid C is at least one selected from itaconic acid, citric acid, glutaric acid, succinic acid, citraconic acid, maleic acid, malonic acid, malic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, trimesic acid, aconitic acid, and oxaloacetic acid, The amount of the alkoxysilane compound B is 105 to 460 parts by mass based on 100 parts by mass of the alumina hydrate. The amount of the polybasic organic acid C is 1 to 20 parts by mass based on 100 parts by mass of the solid content in the alumina-based composite sol composition.
3. The alumina-based composite sol composition according to claim 1 or 2, wherein: The polybasic organic acid C is at least one selected from itaconic acid, citric acid, glutaric acid, succinic acid, citraconic acid, maleic acid, malonic acid, or malic acid.
4. The alumina-based composite sol composition according to claim 1 or 2, wherein: The alumina sol A containing alumina hydrate is an alumina sol obtained by hydrolysis of aluminum alkoxide.
5. The alumina-based composite sol composition according to claim 1 or 2, wherein: The alumina hydrate has at least one crystal form selected from the group consisting of amorphous, boehmite, and pseudo-boehmite.
6. The alumina-based composite sol composition according to claim 1 or 2, wherein: The alkoxysilane compound B is represented by the following general formula (1): R 1 n (R 3 ) m Si(OR 2 ) 4-m-n (1) In the formula, R 1 represents a group containing an epoxy group or a (meth)acryloyl group, R 2 and R 3 It represents an alkyl group having 1 to 4 carbon atoms, wherein n is in the range of 0 to 2, m is in the range of 0 to 3, and n+m is in the range of 0 to 3.
7. The alumina-based composite sol composition according to claim 1 or 2, wherein: The solvent D is water, alcohol or a combination of water and alcohol.
8. The alumina-based composite sol composition according to claim 1 or 2, wherein: The amount of the alkoxysilane compound B is 250 to 460 parts by mass based on 100 parts by mass of the alumina hydrate in terms of the charging amount. 9 . The alumina-based composite sol composition according to claim 1 or 2 , which is a coating composition. 10 . The alumina-based composite sol composition according to claim 1 or 2 , which is an insulating coating agent or a hard coating agent. 11 . A method for producing an aluminum oxide-based composite thin film, comprising applying the aluminum oxide-based composite sol composition according to claim 1 to a substrate surface and curing the composition.
12. A method for producing an alumina-based composite sol composition, comprising mixing an alumina sol A containing an alumina hydrate, an alkoxysilane compound B, a polybasic organic acid C and a solvent D, The amount of alumina hydrate in the alumina sol A is 3% to 9% by mass, and the alumina hydrate is scaly alumina hydrate particles having a short diameter of 5 nm to 15 nm and a long diameter of 10 nm to 50 nm. The polybasic organic acid C is at least one selected from itaconic acid, citric acid, glutaric acid, succinic acid, citraconic acid, maleic acid, malonic acid, malic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, trimesic acid, aconitic acid, and oxaloacetic acid, The amount of the alkoxysilane compound B is 105 to 460 parts by mass relative to 100 parts by mass of the alumina hydrate in the alumina sol A. The amount of the polybasic organic acid C is 1 to 20 parts by mass based on 100 parts by mass of the solid content in the alumina-based composite sol composition.
13. The method for producing an alumina-based composite sol composition according to claim 12, further comprising a step of producing an alumina sol containing scaly alumina hydrate particles having a short diameter of 5 nm to 15 nm and a long diameter of 10 nm to 50 nm, the step of producing the alumina sol comprising: (1) a step of stirring an aluminum alkoxide having an alkoxy group having 2 to 5 carbon atoms in water at a temperature of 70° C. to 100° C. in the absence of an acid, (2) A step of adding an acid to the reaction solution obtained in the step (1) and stirring the mixture.
Citation Information
Patent Citations
Production of alumina sol
JP1978112299A
Preparation of alumina sol
JP1979116398A
Production of alumina sol
JP1980027824A
Manufacture of alumina sol
JP1984223223A
Coating composition and method for producing alumina thin film
JP2013216760A